Virtual training in mobile plant for turbocharger in oil and gas industry in Kuwait - Alshammar, Majed Gh A H (2019)
Virtual maintenance training or virtual reality (VR) in the industrial and energy industry has been a topic of discussion inside recent years. All major oil and gas companies in recent years have advocated design and develop virtual maintenance training system for the greater benefit of the humanity and the environment focusing on sustainable development. Oil and gas industry often requires people to work in hazardous environments, these environments are constantly increasing in size and complexity as companies look for new more cost effective ways of doing training and maintenance. In this project, a headbased fully immersive virtual reality application is developed in Unity 3D for virtual reality training in industrial equipment maintenance for oil and gas industry. The overall research is done at Kuwait Oil Company (KOC) in which to analyse the crucial part that affecting the production line in oil and gas industry. Turbocharger is an essential link in the oil and gas market, helping industries reduce turnaround times and increase productivity across all spheres of operation. The scopes of works are focused on the development of turbocharger parts. The aim of this project is to design and develop virtual reality (VR) system for turbocharger maintenance training in oil and gas industry, evaluate the efficiency of the implementation of training through the Virtual Reality (VR) system and compare between the process performances data in conventional method. Virtual Reality (VR) application development of a turbocharger has been done by using 3D modelling software, animation software and Unity platform software. The effectiveness of the developed VR training platform was also studied. Experiments were done to evaluate the effectiveness and acceptance level of a virtual reality application in inspection and maintenance compared to conventional turbocharger maintenance training. Validation on this developed virtual reality maintenance training application is done based on five aspects which are functionality, reliability, usability, efficiency, maintainability and portability. VR software developed was evaluated by 20 experts in the oil and gas industry. Result from app validation shows that the functionality aspect offer the best value with 56% and followed by usability with 52%. Respondents verified that they gain beneficial input and experience in VR training platform compared to the manual maintenance method. The results obtained from this study, support the application of learning and training method of using VR system for a particular assembly task and the implemented is expected to highly benefit the industries and maintenance sectors. The possibility of implementing this technology, especially in industrial and maintenance sectors would lead and benefit both organizations in training new procedure or task.